Family Dispute Settlement In Islam: A Study of the Novel “Ipar Adalah Maut” - Anna Hadiyatullah Mahesy; Qurrotul Ainiyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article aims to provide an overview to all interested parties in solving problems in the family and analyze the resolution of family disputes from an Islamic perspective through the study of the novel